Antihypertensive Activity of Black Garlic Extract in Rats and Its Phytochemical Analysis using GC-MS - Daru Estiningsih; Moch Saiful Bachri; Laela Hayu Nurani; Muhammad Ma’ruf; Sapto Yuliani; Vivi Sofia; Dian Prasasti (Universitas Airlangga, 2025)
Background: Hypertension is defined as a medical condition where blood pressure rises above 140/90 mmHg. Black garlic is recognized as a natural remedy that may help lower high blood pressure, primarily due to its abundant antioxidant properties, which are believed to inhibit the function of the angiotensin-converting enzyme (ACE) that is essential for regulating blood pressure. Objective: This study aimed to identify the chemical composition of black garlic using GC-MS and assess its antihypertensive effects in rat models. Methods: This study characterized the chemical composition of black garlic using GC-MS (Agilent 7890A) and evaluated its antihypertensive effects in rats. Hypertension was induced by oral administration of NaCl at a dose of 3.75 g/20 g body weight (BW) from day 0 to day 14. Blood pressure measurements were taken on days 0, 14, and 21. Black garlic extract was administered at three dose levels 4.2 mg/20 g BW, 8.4 mg/20 g BW, and 12.4 mg/20 g BW to evaluate dose dependent antihypertensive responses. Statistical analysis included the Kolmogorov-Smirnov test for normality, homogeneity testing, One-Way ANOVA Results: The GC-MS analysis identified 9-octadecenoic acid as the dominant compound in black garlic, accounting for 34.53% of its total composition. The antihypertensive activity test showed that administering black garlic at a dose of 12.4 mg/20 g BW significantly lowered systolic, diastolic, and mean arterial blood pressure while enhancing nitric oxide levels in hypertensive rats. Conclusion: Black garlic has the potential as an effective herbal treatment to lower blood pressure.